5/6+1/12-2/3= 10/9-(8/9+1/6)= (全要递等式,能简算的要简算)
2个回答
5/6+1/12-2/3
=10/12+1/12-8/12
=3/12
=1/4
10/9-(8/9+1/6)
=10/9-8/9-1/6
=2/9-1/6
=4/18-3/18
=1/18
相关问题
用递等式计算,能简算的要简算. 4 5 + 11 15 + 3 10 60.62-(9.2+12.62) 6.8+ 1
递等式计算(能简算的要简算)([1/6]+[1/8])×24
递等式计算,能简算的要简算2.6+1.4×3; &
递等式计算(能简算的要简算):65乘2/5+65乘3/5 75除8/9减35乘4/5 5/12+(5/6减1/12)除9
递等式计算(能简算的要简算):65乘2/5+65乘3/5 75除8/9减35乘4/5 5/12+(5/6减1/12)除9
2/4+5/9+1/6-5/9 能简算要简算
递等式计算.(能简算的要简算)①2.5×3.2×1.25 ②6.06-3.5×0.24 ③60.4-(10+9.6÷0.
用递等式计算,能简算的要简算. (1)8750-45×108 (2)36÷1.5-2.5×1.6 (3)2-[8/9÷5
用递等式计算,能简算的要简算.(1)8470-104×65(2)1.28+9.8+9.72+10.2(3)168.1÷(
用递等式计算(能简算的要简算) 20.9+10.2÷(5.2-3.5) 9.4×[1.28-(1.54-0.31)] 1